Denomi/Nation: envisioning possibilities of reconstructing an alternative Zimbabwe in Muzorewa's 'Rise Up and Walk' - Javangwe, Tasiyana D. (Palgrave-MacMillan, 2016)
Political developments in Zimbabwe in the new millennium have per force called for a re-look at the very concepts that inform the bedrock of nationhood and belonging to the nation state. They call for questions that interrogate the ways in which certain memories and processes have been privileged as constitutive of the elements that gave birth to the Zimbabwean nation. The political whirlwind that became acutely defined between 1997 and 2009 demands that several modes of remembering Zimbabwean nationhood be allowed to contest and be interpreted in different ways in an effort to envisiona better Zimbabwe. The point of departure in such a project is to view nations as products of collective memory that come into being through narrative.